Nuclear and plastidial SNP and INDEL markers for genetic tracking studies of Jacaranda copaia - Sebbenn, Alexandre M.; Blanc-Jolivet, Celine; Mader, Malte; Meyer-Sand, Barbara R. V. [UNESP]; Paredes-Villanueva, Kathelyn; Honorio Coronado, Euridice N.; Garcia-Davila, Carmen; Tysklind, Niklas; Troispoux, Valerie; Delcamp, Adline; Degen, Bernd (Springer, 2019)
Nuclear and plastidial single nucleotide polymorphism (SNP) and INDEL markers were developed using restriction associated DNA sequencing (RADSeq) and low coverage MiSeq genome sequencing for population genetics and timber tracking purposes in the Neotropical timber species Jacaranda copaia. We used 407 nuclear SNPs, 29 chloroplast, and 31 mitochondrial loci to genotype 92 individuals from Brazil, Bolivia, French Guiana, and Peru. Based on high amplification rates and genetic differentiation among populations, 113 nuclear SNPs, 11 chloroplast, and 4 mitochondrial loci were selected, and their use validated for genetic tracking of timber origin.
Keywords: DNA fingerprints; Geographical origin; MiSeq; RADSeq; Tropical timber; MassARRAY; Jacaranda copaia